Evaluation of Early Childhood Learning Using the Independent Curriculum - Makulua, Korlina; Pattiruhu, Claudia Monique; Mukaddamah, Ivon; Touwe, Yohana S; Huriah, Lilik (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
In this era, education is needed to support children in continuing the next generation of the nation. In education today, an update in education is needed, in order to change education in Indonesia to be more advanced. To achieve the goal of more advanced education, there must be a curriculum update in Indonesia. In February 2022 last year, the Ministry of Education and Culture launched an independent curriculum where the independent curriculum method refers more to the talents and interests of children. This independent curriculum allows students to choose the lessons they like or are most interested in. The purpose of this study is to evaluate early childhood learning on the use of the independent curriculum. This research method uses quantitative methods, this data is obtained from interviews to kindergartens. The results showed that the independent curriculum is very good in supporting students' learning in improving skills, character, by using flexible learning. From this research it can be concluded that the use of an independent curriculum for early childhood is very effective and efficient. The independent curriculum leads to the development of skills and character, focuses on essential material, and uses flexible learning. The limitation of this research is that researchers only conducted research in one kindergarten in 50 cities in West Sumatra Province, researchers hope that future researchers can conduct research with a wider range so that they can continue this research. This study also recommends to future researchers as a reference in conducting research on the use of Merdeka Curriculum in Early Childhood.